Feeding ecology is the primary driver of beak shape diversification in waterfowl. (30th May 2017) - Olsen, Aaron M.
Summary: The diversity of beak shapes among birds is often assumed to be largely the result of adaptations to different feeding behaviors and diets. However, this assumption has only been tested for a small subset of avian diversity, primarily within the order Passeriformes. Moreover, given the role of the beak in behaviors other than feeding and given that most previously identified beak‐feeding associations concern beak size rather than shape, it remains unclear how much of beak shape diversity is explained by feeding ecology and what functional explanations account for these differences in shape. I quantified the association between beak shape and feeding ecology for 42 species in the bird order Anseriformes (waterfowl) using 3D curvature of the upper beak collected from museum specimens and continuous dietary data compiled from the literature. I also tested whether leverage or stress resistance of the beak explains the association between beak shape and feeding ecology. Diet is strongly and significantly correlated with beak shape in waterfowl. An ancestral beak shape reconstruction and the reconstructed diet of the anseriform fossil Presbyornis both support filter‐feeding as ancestral for most waterfowl, followed by multiple, significantly convergent transitions from a duck‐like beak toward a more goose‐like beak. The evolution of a more goose‐like beak is associated with increased consumption of leaves, decreased consumption of invertebrates, and an increase in mechanical advantage of the beak. Moreover, no association was identified between size (measured as either beak size or body mass) and feeding ecology nor between size and beak shape. These results demonstrate that feeding ecology has acted as the primary selective force in the diversification of waterfowl beak shapes, including the convergent originations of geese. Thus, rapid and convergent adaptation of the beak to feeding is not limited to passerines nor is it limited to size‐correlated shape changes. The positive evolutionary correlation between mechanical advantage and herbivory shows that lever mechanics can explain the functional evolution of the kinetic upper beak in birds. These results also suggest that functions of the beak other than feeding may play a minor role in explaining overall beak shape diversity. A lay summary is available for this article. Abstract : Lay Summary